A review on cement concrete strength incorporated with agricultural waste. (2023) - Gudainiyan, Jitendra; Kishore, Kamal
Abstract: The agricultural sector accounts for over 58% of the total GDP of India. Nearly 16% of India's GDP comes from this industry (GDP). India's agriculture industry has flourished because of the country's abundant arable land and variety of suitable growing environments. Studies show that agricultural waste material, when properly processed, possesses the pozzolanic properties which makes them suitable to be utilized as a partial substitute of cement content by weight in the production of cement concrete. In the present study, the availability and effect of agricultural wastes on the strength of cement concrete has been discussed and it was found that partial substitution of agricultural waste materials such as sugarcane bagasse ash, rice husk ash and palm oil fuel ash with cement content can reduce annual global consumption of cement by approximately 121 million tons, while maintaining the desirable properties of cement concrete.